2010
DOI: 10.3109/08037050903525103
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour ambulatory heart rate and organ damage in primary hypertension

Abstract: An elevated nocturnal HR, > or = 65 bpm, obtained with ABPM registry, is associated with the presence of TOD in hypertensive patients. ABPM is a powerful tool for hypertensive patients not only to monitor BP control but also to obtain information on HR which may provide additional information about current and future cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
1
15
0
2
Order By: Relevance
“…Fácila et al [17] studied a sample of 566 hypertensive patients, assessing HR by ABPM during activity and resting periods, and analyzing the association with the presence of TOD. The prevalence of TOD was found to be 12.4%, versus 46.7% in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fácila et al [17] studied a sample of 566 hypertensive patients, assessing HR by ABPM during activity and resting periods, and analyzing the association with the presence of TOD. The prevalence of TOD was found to be 12.4%, versus 46.7% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, proteinuria values may be increased in subjects with an elevated HR, even in normotensive individuals [15]. The association of HR (both sleep and awake HR) and its variability with vascular, renal and cardiac target organ damage (TOD) in a cohort of hypertensive patients has not been clearly established [16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…24 In a Japanese study, subjects with a higher HR had higher frequencies of proteinuria, although they were all normotensive, indicating that subjects with elevated HR are likely to have early-stage vascular damage, even if they are normotensive. 25 In hypertensive patients assessed with 24-hour ambulatory monitoring, Facila et al 26 showed that patients with nocturnal HR Ն65 bpm (41.3%) had a higher prevalence of target organ damage compared with those with HR Ͻ65 bpm. HR was also shown to be a main determinant of arterial stiffness.…”
Section: Hr As a Determinant Of Target Organ Damagementioning
confidence: 99%
“…The ABP-International study found in 7600 untreated patients with hypertension that every 10 bpm of HR increase during nighttime could be associated with 13% of increased risk of cardiovascular events [15]. Another study in 566 patients with hypertension showed that nighttime HR values above 65 bpm could be associated with the presence of target organ damage [16].…”
Section: Introductionmentioning
confidence: 99%